تطوُّر دَلالَتَي "الجاريـة" و"الحـجّ" عند ابن فارس - قلالـة, عمار (حوليات المخبر, 2016)
حَكَمَ اللغوي أحمد بن فارس بتطوِّرٍ قديمٍ لدلالتي "الجَارِيَة" و"الحَجّ" من غير أن يورد برهانا على ذلك. وهذا المقال تحقيق في صحَّة هذين الحُكْمَين من خلال مرجعين اثنين أحدهما: الشواهد الفصيحة الصحيحة والثاني: أقوال العلماء الأثبات في شأن تينك اللفظتين فالشواهد وحدها لا تكفي للجزم؛ لقلَّة ما بلغنا منها من الأزمن المواضي. وأقوالُ العلماء وحدها غير كافية لميز الضعيف من الصحيح؛ لأنهم لا يصرِّحون غالبا بمستندهم في إطلاق تلك الأحكام. لكن اتفاق أكثرهم على قول ومجيء الشواهد مصدَّقة له يجعله راجحا مقبولا إلى أن يثبتَ خلافُه. “Ibn Faris” argue that the meanings of the words “El Jariya” (the maid). and “El Hadj” (The Pilgrimage) has been changed since ancient times. but he never gave proof of that . The objective of this article is to confirm Ibn Faris’s opinion about these words through two references. the first are the texts that reference to them. the second is the opinion of the scholars; considering the texts alone is not enough on the account that there are few of them. and the opinion of the scholars is not enough as well because they do not provide any proof. but if the opinions matched the texts that could be considered as a valid reference.